Retained Students and Classmates' Absences in Urban Schools. (December 2013) - Gottfried, Michael A.
Research in grade retention has predominantly focused on the effect of this practice on the retained student. This study contributes to the limited body of research examining the effect of retained classmates on the outcomes of other students in the same classroom. Using a longitudinal data set of all elementary school students in a large urban school district, this study evaluates how the percentage of retained classmates affects other students' absence patterns, both unexcused and excused. Focusing on absences as an outcome is key, as they signal educational disengagement and highly correlate with schooling and lifelong success. Based on quasi-experimental methods, the results indicate that a greater percentage of retained classmates increases other students' absences. The effect is only present on unexcused absences, not excused absences, hence signaling an increase in disengagement in other students. Individual- and classroom-level moderating effects are evaluated, and policy implications for classroom assignment are discussed.